1995
DOI: 10.2307/1591871
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Molecular Characterization of V-Factor (NAD)-Independent Haemophilus paragallinarum

Abstract: In South Africa from early 1989 onward, strains of Haemophilus paragallinarum not requiring nicotinamide adenine dinucleotide (NAD) have been isolated from commercial chickens suffering from infectious coryza. Fifteen of these field isolates were characterized by biochemical typing, serotyping, restriction endonuclease analysis (REA), and ribotyping. The chosen isolates represented diversity in geographic location, time of disease outbreak, and type of flock. All were typical of the species in biochemical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The available DNA-DNA hybridization data of Mouahid et al (1992), who reported 89 % DNA binding between strain ATCC 29545 T and the biovar 2 strain SA 4461, indicate that the biovar 1 and 2 forms of Avibacterium ([Haemophilus]) paragallinarum can be accommodated in one species. The DNA fingerprinting work of Miflin et al (1995) has provided evidence that the South African NAD-independent isolates of Avibacterium ([Haemophilus]) paragallinarum are clonal, indicating that the DNA-DNA hybridization data for strain SA 4461 are applicable for all of the biovar 2 strains in this study. As well, all South African biovar 2 isolates of Avibacterium ([Haemophilus]) paragallinarum tested to date have yielded a positive reaction for the [Haemophilus] paragallinarum-specific PCR (Chen et al, 1996;Miflin et al, 1999).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…The available DNA-DNA hybridization data of Mouahid et al (1992), who reported 89 % DNA binding between strain ATCC 29545 T and the biovar 2 strain SA 4461, indicate that the biovar 1 and 2 forms of Avibacterium ([Haemophilus]) paragallinarum can be accommodated in one species. The DNA fingerprinting work of Miflin et al (1995) has provided evidence that the South African NAD-independent isolates of Avibacterium ([Haemophilus]) paragallinarum are clonal, indicating that the DNA-DNA hybridization data for strain SA 4461 are applicable for all of the biovar 2 strains in this study. As well, all South African biovar 2 isolates of Avibacterium ([Haemophilus]) paragallinarum tested to date have yielded a positive reaction for the [Haemophilus] paragallinarum-specific PCR (Chen et al, 1996;Miflin et al, 1999).…”
mentioning
confidence: 70%
“…As well, all South African biovar 2 isolates of Avibacterium ([Haemophilus]) paragallinarum tested to date have yielded a positive reaction for the [Haemophilus] paragallinarum-specific PCR (Chen et al, 1996;Miflin et al, 1999). Furthermore, all of the South African biovar 2 isolates that have been serotyped (Miflin et al, 1995) have been allocated to the existing Page serotyping scheme, which was originally created using typical biovar 1 strains (Page, 1962). Hence, there are a number of separate bodies of evidence -the DNA-DNA hybridization data of Mouahid et al (1992), the clonality of the South African biovar 2 isolates as shown by Miflin et al (1995), the positive reaction in the [Haemophilus] paragallinarum PCR (Chen et al, 1996, Miflin et al, 1999, the ability to assign the South African isolates of biovar 2 to the existing [Haemophilus] paragallinarum serotyping scheme (Miflin et al, 1995) and the 16S rRNA gene sequencing results of the current study -that all support the inclusion of the biovar 2 Table 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These include strains of Actinobacillus pleuropneumoniae, which causes pleuropneumonia in swine (22); Haemophilus paragallinarum, which causes fowl choryza (1,15); Haemophilus parainfluenzae, which can cause pneumonia and meningitis in humans (7); and Haemophilus ducreyi, which causes the sexually transmitted disease chancroid in humans (26,27). In H. parainfluenzae, H. paragallinarum, and H. ducreyi, V-factor independence has been shown to be encoded on a plasmid (1,27,28).…”
mentioning
confidence: 99%
“…A recent study has successfully utilized ribotyping to demonstrate that growth factor-independent isolates of H. paragallinarum recently reported in South Africa have little genetic diversity, unlike the classic H. paragallinarum strains also present in that country which show considerable diversity (Miflin et al, 1995). When developing ribotyping methods for a particular species, it may be necessary to investigate the usefulness of a number of different restriction endonucleases.…”
Section: Discussionmentioning
confidence: 99%